SOPHROLOGY, PSYCHOSOMATICS, DEONTOLOGY AND CREATIVITY - Miroslav Prstačić (Research in Education and Rehabilitation)
Ancient and contemporary reflections on Man’s consciousness, on psychosomatics, spirituality and man’s creative and/or destructive impulses can be considered as his permanent need to understand the sources, beginnings and meaning of existence, the miracles of nature and the connection between mind and body. The results of the study of the anthropological traits of perception, imagination, and creativity in various disciplines of art and science reveal that the experience of aesthetic pleasure arises from biological needs, the symbolic values of the object, and the distant analogies of archetypal images in the planetary mind of man. The archetypal primordial feature of the imagination contained in itself, probably as early as the Neolithic, an intuited germ of archaic humanism, which later, together with the discovery of consciousness for the concept of the soul and the sacred, would appear in the thought of Buddha, Lao-Tzu, Zoroaster, Christ and Mohammed, as well as in many other traditional beliefs and legacies in the human mind. In this context, culture can be considered as a way of life that encompasses beliefs and religiosity, rituals and various arts (music, theatre, poetry, painting, dance…) mentality and patterns of historically transmitted symbols. At the same time, speech is marked by all physical, psychosomatic, psycho-emotional and spiritual manifestations and is the origin of hermeneutics itself. On this path, hierarchical relations in science are manifested in the development of traditional and new scientific disciplines, in the constant discovery of enigmas about Man and the World, while the primordial and magical power of various arts constantly enters the metaphysical field of consciousness as a form of energetic, symbolic and aesthetic expression of the life potentials. Following the idea and reflections of Professor Caycedo in the sense of "Ut conscientia noscatur" / "That consciousness may be known," sophrology (an elegant neologism) is presented as an innovative thought and a complementary discipline (science and philosophy) of a new era. It focuses on studying the interconnectedness of mind, body, the nature of life potentials, and human creativity, utilizing holistically conceived deep-ecological, transcultural, psychosomatic, and trans-disciplinary approaches and methods with educational, prophylactic, and/or therapeutic goals. The content is considered within the framework of the following complementary themes: Antoine de Saint-Exupéry's The Little Prince and Friedrich Nietzsche's Thus Spoke Zarathustra; Sayings/proverbs in the culture of the Igbo people in Nigeria, rendered into verses in the form of Japanese haiku poetry; Sophrology – a complementary discipline of a new era on consciousness and creativity; Ut pictura poesis: excerpts from a Croatian-French clinical study in the field of psychosocial oncology, sophrology, and creative art therapy; Bioethics and deontology with a review of reflections on interdisciplinarity, art, the mission of the European consortium EcARTE, applied cognitive science (ACS), and related fields.